A study of space creation for healing landscape design in the post-epidemic era - Ren, Qiugang; Weng, Yueyue; Hu, Zhixiong (Frontiers in Psychology, 2025)
This study explores the spatial creation strategy of healing landscape design in the post epidemic era and identifies four types of key design elements: ecological environment elements, spatial organization elements, sensory experience elements, and social interaction elements through literature research and multi-case analysis. The study compares and analyzes domestic and international cases such as Jurong Lake Garden in Singapore, Cleveland Clinic Healing Garden, Shenzhen Bay Park "Garden of the Heart" and Liangzhu Hospital Healing Garden in Hangzhou and proposes strategies for healing landscape design at the city scale, community scale and site scale. It is found that successful healing landscapes need to integrate the principles of biophilic design, adaptive resilience, sensory calibration, social granularity, and cultural resonance, and provide solutions to promote public health and community resilience through multi-scale healing networks, micro-healing spaces, healing waterscapes, and resilient healing infrastructures.